ALAT BANTU AJAR SISTEM TUBUH MANUSIA UNTUK SISWA KELAS XI SEKOLAH MENENGAH ATAS (SMA) - Reny Wahyuning Astuti (JURNAL AKADEMIKA)
System of the human body is a combination of organs that perform certain functions. Material humanbody systems, including the biology lesson at high school level (high school) class XI in particular. This studyaims to develop learning aids the human body system for students of classes XI multimedia-based high school in order to provide convenience to the students to understand the material system of the human body during this tedious method of learning so that students difficulties are used to understand and remember the material that has been taught. This teaching tool is built using Macromedia Flash 8 Professional. The data input is the material that covers the human body system circulatory system, digestion, respiration, and excretion. The materials will be displayed in the form of text, sound, images and animation. This teaching tool is interactive, which is equipped with a specific exercise. The results showed that this kind of teaching aids used in teaching and learning at the course from high school biology class XI in particular, to provide a new way that is more interactive and not boring with multimedia-based display